Pain in acute hepatic porphyrias: Updates on pathophysiology and management - Kazamel, Mohamed; Pischik, Elena; Desnick, Robert J. (Frontiers in Neurology, 2022)
Acute hepatic porphyrias (AHPs) typically present with recurrent attacks of severe abdominal pain and autonomic dysfunction. While chronic symptoms were historically overlooked in the literature, recent studies have reported increased prevalence of chronic, mainly neuropathic, pain between the attacks. We characterize acute and chronic pain as prominent AHP manifestations and discuss their pathophysiology and updated management. In addition to the abdominal pain, patients could experience headache, low back, and limb pain during attacks. Chronic pain between the attacks is typically neuropathic. δ-aminolaevulinic acid (ALA) plays a major role in acute and chronic pain via its neurotoxic effect, especially where the blood-nerve barrier is less restrictive i.e., the autonomic ganglia, nerve roots, and free nerve endings. For earlier diagnosis, we recommend testing a spot urine porphobilinogen (PBG) analysis in any patient with recurrent severe acute abdominal pain with no obvious explanation, especially if associated with neuropathic pain, hyponatremia, dysautonomia, or encephalopathy. It is mandatory to exclude AHPs in any acute painful neuropathy. Between the attacks, testing for AHPs should be considered for patients with a past medical history of acute/subacute neuropathy, frequent emergency room visits with abdominal pain, and behavioral changes. Pain during the attacks should be treated with opiates combined with hemin infusions. Symptomatic treatment of chronic pain should start with gabapentinoids and certain antidepressants before opiates. Givosiran reduces levels of ALA and PBG and likely has long-term benefits for chronic pain, especially if started early during the course of the disease.